RPD3 and UME6 are involved in the activation of PDR5 transcription and pleiotropic drug resistance in ρ0 cells of Saccharomyces cerevisiae - Yoichi Yamada (BMC, 2021)
Abstract Background In Saccharomyces cerevisiae, the retrograde signalling pathway is activated in ρ0/− cells, which lack mitochondrial DNA. Within this pathway, the activation of the transcription factor Pdr3 induces transcription of the ATP-binding cassette (ABC) transporter gene, PDR5, and causes pleiotropic drug resistance (PDR). Although a histone deacetylase, Rpd3, is also required for cycloheximide resistance in ρ0/− cells, it is currently unknown whether Rpd3 and its DNA binding partners, Ume6 and Ash1, are involved in the activation of PDR5 transcription and PDR in ρ0/− cells. This study investigated the roles of RPD3, UME6, and ASH1 in the activation of PDR5 transcription and PDR by retrograde signalling in ρ0 cells. Results ρ0 cells in the rpd3∆ and ume6∆ strains, with the exception of the ash1∆ strain, were sensitive to fluconazole and cycloheximide. The PDR5 mRNA levels in ρ0 cells of the rpd3∆ and ume6∆ strains were significantly reduced compared to the wild-type and ash1∆ strain. Transcriptional expression of PDR5 was reduced in cycloheximide-exposed and unexposed ρ0 cells of the ume6∆ strain; the transcriptional positive response of PDR5 to cycloheximide exposure was also impaired in this strain. Conclusions RPD3 and UME6 are responsible for enhanced PDR5 mRNA levels and PDR by retrograde signalling in ρ0 cells of S. cerevisiae.